Characterization of the sensory nerve action potential of the Sural Nerve in patients over 60 years of age without peripheral neuropathy (2021)
ABSTRACT: Background: Demonstration of the possibility to obtain the sensory nerve action potential (SNAP) of sural nerve in patients over 60 years old, without peripheral neuropathy. Methods: Prospective study on 101 patients between ages 60 and 90. Stimulation was applied 12 cm proximal to the recording point. Results: 202 SNAPs of the sural nerve were collected with an average peak latency of 3.2 ms, base latency of 2.6 ms, peak-to-peak amplitude of 15.2 μV and velocity of 45.7 m/s Conclusions: It was possible to obtain the sural nerve SNAP in all tested patients older than 60, without peripheral peripheral neuropathy. The values obtained in the study prove to be useful as reference in the evaluation of patients older than 60 years of age.